Equine seminal plasma and sperm membrane: Functional proteomic assessment - Guasti, P. N. [UNESP]; Souza, F. F. [UNESP]; Scott, C. [UNESP]; Papa, P. M. [UNESP]; Camargo, L. S. [UNESP]; Schmith, R. A. [UNESP]; Monteiro, G. A.; Hartwig, F. P. [UNESP]; Papa, F. O. [UNESP] (Elsevier, 2020)
During ejaculation, a large amount of seminal plasma proteins interact with the sperm membrane, leading to a series of biochemical and structural changes implicated in sperm function and gamete interaction. However, the roles of the majority of these proteins remain unknown. This study aimed to investigate the proteome and functionality of the major equine proteins of seminal plasma and the sperm membrane. Seminal plasma and enriched-membrane proteins (150 μg) were separated by two-dimensional gel electrophoresis, and the respective maps were analyzed. Protein identification was performed by in-gel digestion and tandem mass spectrometry (GeLC-MS/MS). Samples were also submitted to in-solution digestion (complex protein mixture) and identified by shotgun analysis by LC-MS/MS; bioinformatic tools were used to investigate protein functions. Seminal plasma and sperm membrane extract maps contained 91.0 ± 8.2 spots and 245.3 ± 11.3 spots, respectively, within the 3–10 pH range. In total, the most abundant proteins identified in 2D maps and in complex protein mixtures included 24 proteins for seminal plasma and 33 for sperm membrane extract, with a high degree of confidence (P < 0.05). Of these, HSP1, CRISP3 and KLK1E2 were the most abundant in seminal plasma; HSP1 was highly abundant in sperm membrane extract, in many isoforms, which is related to membrane destabilization and may compromise sperm preservation. HSP1-polybromo-1 interactions suggested a role in DNA stabilization. Prosaposin was identified in seminal plasma and may play a role in the fertilization process. IZUMO4, a member of the IgSF family involved in the prefertilization stages, was identified in 2D gel and MS/MS analysis of sperm membrane extract. Ten proteins of seminal plasma were found to interact with the sperm membrane and were related to binding and catalytic activities (clusterin, CRISP3, epididymal sperm-binding protein 1, kallikrein1E2, seminal plasma protein A3, and HSP1). Additionally, other identified proteins were associated with DNA integrity, capacitation and recognition of pregnancy. These findings indicate that the binding of specific proteins to the plasma membrane during ejaculation may influence sperm survival after cryopreservation and may play a role in decreasing the quality in stallions with toxic seminal plasma. Elucidation of these interactions is an important step in understanding the biological processes related to equine fertility and facilitates future investigations on the selection and application of low freezability semen strategies.
Keywords: Cryopreservation; Equine; Fertility; Proteome; Semen